The Key Determinants of Brand Loyalty in Indonesia's Cosmetics Market - Anatasia, Velly; Tannia, Tannia; Robert, Alexander; Florencia, Livia Evangelina (Dinasti Publisher, 2025)
The global annual spending on cosmetics is estimated to be around billions, with numerous industry players competing fiercely to expand their market share. Companies in the cosmetics sector aim to secure a leading position by fostering customer loyalty, which is closely linked to brand loyalty. As a result, brand loyalty becomes a crucial factor in achieving success in a highly competitive market. This study investigates the impact of brand loyalty on the purchasing behavior of female consumers in Jakarta, the capital city of Indonesia. The research focuses on seven aspects of brand loyalty: brand name, product quality, price, design, promotion, service quality, and store environment. This study utilizing descriptive analysis, factor loading, and multiple regression methods to tested its hypotheses. Data was collected through self-administered questionnaires distributed to 125 female respondents who regularly use cosmetics. The findings revealed a strong correlation between promotion and brand loyalty. Additionally, the results demonstrated a positive and significant relationship between the factors of brand loyalty (brand name, product quality, price, design, promotion, service quality, and store environment) and loyalty to cosmetic brands.